COLLECTIVE URGENCY TUTELA ANTECEDENT IN PUBLIC CIVIL ACTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This essay seeks to delineate the path of stabilization of antecedent tutelage precedent in public civil action. The evolution of the Brazilian collective process microsystem and the provisional protections provided for in CPC / 2015 is analyzed. The specific problem that will be dealt with concerns the relevance brought in the stabilization of the anticipated tutelage required beforehand in the public civil action and the difficulties regarding the stability and the problematic of the res judicata. From the above, it is concluded that these institutes are perfectly adequate and applicable to the collective process, cooperating for the maximum effectiveness of homogeneous diffuse, collective and individual protection, whose guidelines are considered one of the most sensitive subjects because they involve unavailable rights. (Art. 5, caput, of CF / 88).